Program Indonesia Pintar (PIP) di Madrasah Aliyah Laboratorium UIN Sumatera Utara (Evaluasi Program Menggunakan Model Evaluasi CIPP) - Nurul Farhaini; Amiruddin Siahaan; Muhammad Rifa’i (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study focused on evaluating the smart Indonesia program implemented in Madrasah Aliyah Laboratory UIN North Sumatra. The Indonesia Pintar Program is an education funding program for underprivileged Didi participants. This research uses descriptive qualitative research methods and is analyzed specifically with the CIPP program evaluation model (context, input, process, product). Data are collected through observation, interviews, questionnaires, documentation. The findings of this study highlight the smart Indonesia program with 4 aspects of the CIPP program evaluation model including: 1) contex evaluation, suitability of PIP recipient targets at UIN SU MALL, 21 class XII students received Rp.900,000. 2) input evaluation, there are 2 PIP organizers at UIN SU MALL, but there are no special PIP facilities. 3) process evaluation, the PIP process is carried out in accordance with PIP technical instructions, but the madrasah has not implemented the preparation of PIP realization reports, 4) product evaluation, PIP fund realization is in accordance with the provisions for the utilization of PIP funds even though there is no significant impact on student attitudes, but has an impact on the motivation of students' enthusiasm to continue their education